Tillich on Divine Power and Ultimate Meaning in Human History - Hammond, Guy (Laval théologique et philosophique)

(untitled) (Faculté de philosophie, Université Laval, 2011)
Paul Tillich’s concept of God opposes the “interventionist” model of traditional Western theism. This paper attempts to determine whether, and in what sense, for Tillich, God may be said to act specifically to influence the course of historical events. It is argued that his concept of “Spiritual power” provides his answer. In clarification the concepts of “spirit,” “power,” “meaning,” “vocation,” “kairos,” and “the renunciation of power” are explored. According to Tillich, the vocations of specific social groups are empowered by divine power, providing both gift and task. For Christians the vocation of Jesus the Christ to proclaim the coming Kingdom of God as the ultimate meaning of history provides the criterion by which concrete vocations may be judged. God acts by providing meaning, which must be chosen and achieved.